RhoGAP RGA-8 supports morphogenesis in C. elegans by polarizing epithelia - Raduwan, Hamidah (Biol Open, 2020)
CDC-42 regulation of non-muscle myosin/NMY-2 is required for polarity maintenance in the one-cell embryo of Caenorhabditis elegans. CDC-42 and NMY-2 regulate polarity throughout embryogenesis, but their contribution to later events of morphogenesis are less understood. We have shown that epidermal enclosure requires the GTPase CED-10/Rac1 and WAVE/Scar complex, its effector, to promote protrusions that drive enclosure through the branch actin regulator Arp2/3. Our analysis here of RGA-8, a homolog of SH3BP1/Rich1/ARHGAP17/Nadrin, with BAR and RhoGAP motifs, suggests it regulates CDC-42, so that actin and myosin/NMY-2 promote ventral enclosure during embryonic morphogenesis. Genetic and molecular data suggest RGA-8 regulates CDC-42, and phenocopies the CDC-42 pathway regulators WASP-1/WSP-1 and the F-BAR proteins TOCA-1 and TOCA-2. Live imaging shows RGA-8 and WSP-1 enrich myosin and regulate F-actin in migrating epidermal cells during ventral enclosure. Loss of RGA-8 alters membrane recruitment of active CDC-42. We propose TOCA proteins and RGA-8 use BAR domains to localize and regenerate CDC-42 activity, thus regulating F-actin levels, through the branched actin regulator WSP-1, and myosin enrichment. RhoGAP RGA-8 thus polarizes epithelia, to promote cell migrations and cell shape changes of embryonic morphogenesis.